(untitled) (Innovaciones Educativas, 2022)
Technical Vocational Education and Training (TVET) in Costa Rica has received great social, political, and economic attention due to the growing need for skilled labor in different sectors to diversify the economy and reduce social inequalities. Furthermore, the current level of unemployment, especially among young people, shows the importance of initial vocational training and draws attention not only to the political agenda but also to the constant discussion about the importance and role of teachers who train future professionals in Costa Rican TVET. Among other things, there is a need for qualified teachers who know the characteristics and specificities of TVET and can respond with pedagogical and didactic competencies. This work examines the role and importance of TVET for Costa Rica and its teachers in this context. Furthermore, we considered the example of the bilateral project Costa Rica-Germany entitled: Technical Vocational Education and Training in Costa Rica (CoRiVET). Among the main conclusions is that the training for the faculty in TVET in Costa Rica shows weaknesses in the pedagogical domain, professional didactics, and teacher training, which are among the most urgent challenges to be resolved in order to strengthen the system, as well as the development of competencies through training programs.